Improved precise time-step integration algorithms for solving dynamic problems - Chen, Zhenlin (2010)
A study on the properties of the precise time-step integration methods for the simulation of dynamic responses of engineering systems is presented in this thesis. The improved precise time-step integration algorithms can reduce the computational cost significantly and maintain the accuracy as well.